Problems and forecasts of the strategic development of enterprises in the context of sanctions restrictions - Larin S. N., Znamenskaia A. N. (Science and education: future development, 2018)
A brief analysis of the impact of sanctions restrictions on the development of industrial enterprises has been carried out. Sources of intra-corporate strategic development of industrial enterprises as independent economic entities are proposed, taking into account the peculiarities of the impact of sanctions restrictions and other factors of external instability.
Keywords: развитие; российская экономика; стратегическое планирование; промышленные предприятия; development; strategic planning; Russian economy; санкционные ограничения; sanctions restrictions; industrial enterprises